1995
DOI: 10.1111/j.1365-2141.1995.tb05427.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of human parvovirus B19 DNA detection in blood donors

Abstract: 1000 serum samples from blood donors were tested for human parvovirus B19 (B19) DNA by a nested PCR assay: six samples were positive for B19 DNA. The frequency was 1/167 (0.6%), considerably higher than previous surveys (0.004-0.03%). Five of the six samples were also positive for anti-B19 IgM, indicating an acute phase of infection. It is recommended to screen for B19 DNA in blood products to prevent transfusion mediated viral infection for those susceptible such as immunocompromised patients and pregnant wom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
52
1
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 11 publications
2
52
1
4
Order By: Relevance
“…Testing minipools of 10 instead of 50 to 1,200 plasma samples also affected detection. For pools of 10 plasma samples, Yoto et al found a 0.6% prevalence of erythrovirus DNA with a nested PCR assay that had a sensitivity of 100 genome equivalents (geq)/ml (42). The recent identification of at least three fairly distant human erythrovirus genotypes might also have played a role in estimations of the prevalence of circulating viral DNA (35).…”
Section: Discussionmentioning
confidence: 99%
“…Testing minipools of 10 instead of 50 to 1,200 plasma samples also affected detection. For pools of 10 plasma samples, Yoto et al found a 0.6% prevalence of erythrovirus DNA with a nested PCR assay that had a sensitivity of 100 genome equivalents (geq)/ml (42). The recent identification of at least three fairly distant human erythrovirus genotypes might also have played a role in estimations of the prevalence of circulating viral DNA (35).…”
Section: Discussionmentioning
confidence: 99%
“…Esta frecuencia se encuentra entre las más altas reportadas previamente en la literatura para este tipo de poblaciones y es cercana a la descrita por Yoto y cols, quienes notifi caron una frecuencia de 1 en 167 y Candotti y cols, que encontraron un rango 0,55 a 1,3% 11,18 . No obstante, otros autores han documentado presencia de ADN de B19 en un amplio rango de frecuencias, las que fl uctúan entre 1 en 35.000 y 1 en 625 10,[19][20][21][22] .…”
Section: Discussionunclassified
“…El uso de grandes lotes de plasmas, con la consecuente dilución de las muestras, puede resultar en una subestimación de la presencia de ADN viral por pérdida en la detección de aquellos casos con niveles bajos de viremia 11 . Esto concuerda con el hecho de que los estudios que revelan frecuencias de detección más altas, coinciden en la utilización de pequeños lotes de no más de 10 plasmas, con el fi n de evitar el problema de dilución.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…With techniques like PCR, the frequency of a viremic blood donation ranges from 1:167 (Santagostino et al 1994, Yoto et al 1995 to 1:1420 during seasonal outbreaks (Schmidt et al 2001) and from 1:5950 to 1:30000 off-season , McOmish et al 1993, Schmidt et al 2001.…”
Section: Discussionmentioning
confidence: 99%